Microsoft Certified Azure AI fundamentals crash course (O'Reilly Media, Inc., 2022)
Artificial intelligence is no longer an abstract concept. It’s being used here and now by companies of all sizes and industries. To meet the growing demand for AI and machine learning professionals, Microsoft has created the Exam AI-900: Microsoft Azure AI Fundamentals. Earning this entry-level certification could help jumpstart your career in one of the most exciting areas of IT. Join expert Emilio Melo to learn everything you need to successfully prepare for the Azure AI Fundamentals exam. You’ll walk through the most important topics on the exam, such as machine learning and cognitive services technologies in vision, NLP, and conversational AI—and identify gaps in your Azure knowledge so that you know exactly what to focus on when getting ready for the exam.